Reflection Leader-Member Exchange In Organizational Commitment A Field research in Ministry of Iraqi Defense - سعيد, هديل كاظم; التميمي, وسام خالد (Journal of Economics and Administrative Sciences, 2016)
AbstractThe researcher seeks, through different aspects of the search, to reach a set of objective concerning in content creation a clear vision about conceptual and practical dimension of relation and effects between (Leader-Member Exchange, and Organizational Commitment) to construct a framework of a pragmatic model as a solution to research problem and it questions. The theoretical problem is derived basically from the scarcity of Arab studies and researches that deal by study and analyses for such important of The two variables blend. The practical problem depends in deriving from reality of every day work in the Iraqi ministry of defense. On this basis, a formula of research problem for purpose of clear vision for reflection leader-member exchange in Organizational Commitment for workers in organizational surveyed, represented Leader-Member Exchange (trust, effect, contribution and respect), and Organizational Commitment (continuous, affective, and normative). Questionnaire has been used to collect data, withdrawal stratified random sample by size (100) individual employees in three d analysis of research data. The results indicate Significant effect Leader-Member Exchange In Organizational Commitment for individuals research sdepartments in the ministry Mentioned, and using statistical program (SPSS) to entry anample. The researchers recommended that the necessity to increase the interest of the ministry, exchanged relationships between Manager and subordinate, By which it can be functional life becomes a typical life filled with love, respect, and appreciation of, or be miserable life filled with hatred, hypocrisy, lack of confidence, reflected it results positively or negatively on subordinates commitment to the organization.